2001
DOI: 10.1002/etc.5620200814
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of lab‐contaminated and native polycyclic aromatic hydrocarbons to the amphipod Corophium volutator relates to chemical desorption

Abstract: In the present study, the relationship between bioavailability of polycyclic aromatic hydrocarbons (PAHs) to benthic amphipods and the PAH desorption kinetics was examined. To that end, field-contaminated sediment was treated in three different ways. One subsample had no addition of PAHs and contained native PAHs only. To a second subsample, six PAHs (phenanthrene, fluoranthene, anthracene, pyrene, benzo[b]fluoranthene, and benzo[k]fluoranthene) were added in the laboratory. Two of the PAHs were added at highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(11 citation statements)
references
References 41 publications
3
8
0
Order By: Relevance
“…In the untreated sediment, we did not expect any significant redistribution between the rapidly and the slowly desorbing compartments during the 35-day exposure period of the oligochaetes, because of two reasons: (i) No significant changes in the rapidly desorbing fractions of PAHs were observed in the 137 weeks interval preceding the exposure (30). (ii) Rapidly desorbing fractions of PAHs in a lab-contaminated sediment were not altered by biota (24). In the treated sediment, however, the rapidly desorbing fraction in the treated sediment increased during the exposure period after the manipulation of the sediment.…”
Section: Figure 1 Biota To Sediment Accumulation Factor (Bsaf) (G Ofmentioning
confidence: 80%
See 4 more Smart Citations
“…In the untreated sediment, we did not expect any significant redistribution between the rapidly and the slowly desorbing compartments during the 35-day exposure period of the oligochaetes, because of two reasons: (i) No significant changes in the rapidly desorbing fractions of PAHs were observed in the 137 weeks interval preceding the exposure (30). (ii) Rapidly desorbing fractions of PAHs in a lab-contaminated sediment were not altered by biota (24). In the treated sediment, however, the rapidly desorbing fraction in the treated sediment increased during the exposure period after the manipulation of the sediment.…”
Section: Figure 1 Biota To Sediment Accumulation Factor (Bsaf) (G Ofmentioning
confidence: 80%
“…The degradation of hydrophobic compounds was strongly related to the amount of chemical desorbing within a specified lapse of time (20)(21)(22). Lamoureux and Brownawell (23) showed a good correlation between the bioavailability of polycyclic aromatic hydrocarbons (PAHs) and linear alkylbenzenes in sediment cores to deposit-feeding clams and the fraction desorbing in 24 h. In a previous study, we demonstrated that 76% of the variability of BSAF of native and freshly added PAHs for deposit-feeding Corophia volutator could be explained by differences in the distribution over rapidly and slowly desorbing fractions (24).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations